Sosialisasi Gemar Menabung Pada Anak-Anak Kelurahan Batakte Melalui Pemanfaatan Barang Bekas Menjadi Celengan - stefanie burin; Ayub A. Mautorin; Klotilda S. Andi; Sarani M. Tulun; Petronela A. Balol; Susana P. Baso; Adrianus Ketmoen (Cv. Utility Project Solution, 2023)
Community service activities are aimed at children so they understand more about the importance of saving from an early age. This activity was carried out for children who live in the Batakte Village, West Kupang District, Kupang Regency. There were 20 participants, starting from Kindergarten, Elementary School Grades 1, 2, 3, and 4. Overall, this activity used the method of socializing, question and answer, and direct practice. These results show, (1) Socialization of saving from an early age has increased children's understanding and insight into the importance of saving from an early age; (2) Training on making piggy banks by utilizing used goods and providing new insights for children as well as fostering creativity and loving the environment by utilizing used goods into ready-to-use goods; (3) Socialization activities for saving from an early age and making piggy banks from used goods to encourage saving from an early age.